Uma proposta de unidade de ensino sobre a antiga Teoria Quântica como instrumento pedagógico alternativo - Carvalho, Alessandro Xavier da Silva (2017)
This work proposes the use of a teaching unit in the form of alternative didactic material on Introduction to Quantum Theory for classes of high school, according with the theoretical foundations of the theories of Piaget, Vigostky and the significant learning of David Ausubel. The didactic experiment was applied to a third year high school class, with 32 students, from the Instituto Federal de Educação, Ciência e Tecnologia de Mato Grosso – IFMT. With the use of videos, conceptual maps, questions and fundamentally the educational product, we seek to discuss the first concepts related to Quantum Theory through dynamic activities and expository classes with the participation of the students. The questions occurred continuously, through direct questions containing concepts relevant to the understanding of quantum theory, containing conceptual and mathematical questions. The results were analyzed through several evaluations. The positive result achieved can be verified mainly in the answers given to the questions made in the evaluation stage V of this work after the presentation of the educational product.